Gender-Specific Transfusion Affects Tumor-Associated Neutrophil: Macrophage Ratios in Murine Pancreatic Adenocarcinoma - Benson, Douglas D. (2010)
INTRODUCTION: Perioperative blood transfusion has been linked to decreased survival for pancreas cancer. Noting clinical data associating female blood products with increased morbidity, our lab has demonstrated that transfusion of female blood augments metastatic events compared to male blood in an immunocompetent murine pancreatic cancer model. It has been suggested that tumor-associated macrophages correlate with tumor progression by promoting angiogenesis. More recently, tumor-associated neutrophils have been implicated in aggressive tumor behavior. We hypothesize that differences in gender-specific transfusion-mediated pancreatic cancer progression are due to microenvironmental changes within the tumor. To test this hypothesis, we examined tumor-associated neutrophils and macrophage ratios in male and female mice with pancreatic cancer receiving blood transfusion from male or female donors. METHODS: C57/BL6 mice, age 7–9 weeks, underwent splenic inoculation with 2.5×10(5) PanO2 murine pancreatic adenocarcinoma cells. Mice were transfused on post-op day 7 with 1 ml/kg supernatant from day 42 male or female packed red cells. Necropsy was performed at 5 weeks or earlier for clinical deterioration, and tumors harvested. Frozen sections (5 μm) were stained for neutrophils and macrophages by immunofluorescence. Data were analyzed using ANOVA; p≤0.05 was used to determine significance; N≥3 per group. RESULTS: Clinically, male mice had greater morbidity and mortality than female mice when receiving female blood products, with roughened hair coat, development of ascites and death due to bowel obstruction. In evaluating the tumor microenvironment from mice receiving female blood products, male mice were noted to have a greater neutrophil to macrophage ratio than female mice, 0.176±0.028 vs. 0.073±0.012, p=0.03. When examining neutrophil to macrophage ratio in mice receiving male blood products, no difference was noted (p=0.48). CONCLUSIONS: Male mice with pancreas cancer have greater morbidity than female mice when receiving female blood products. Furthermore, the difference in neutrophil to macrophage ratio suggests that gender-specific blood transfusion promotes aggressive tumor behavior in male mice via microenvironmental changes. These data warrant further study to delineate sex-related differences in pancreatic cancer progression.